Client-Server and Peer-to-Peer Ad-hoc Network for a Flexible Learning Environment - Khaddage, Ferial; Lattemann, Christoph (International Journal of Interactive Mobile Technologies (iJIM), 2010)
Peer-to-Peer (P2P) networking in a mobile learning environment has become a popular topic of research. One of the new emerging research ideas is on the ability to combine P2P network with server-based network to form a strong efficient portable and compatible network infrastructure. This paper describes a unique mobile network architecture, which reflects the on-campus studentsâ?? need for a mobile learning environment. This can be achieved by combining two different networks, client-server and peer-to-peer ad-hoc to form a sold and secure network. This is accomplished by employing one peer within the ad-hoc network to act as an agent-peer to facilitate communication and information sharing between the two networks. It can be implemented without any major changes to the current network technologies, and can combine any wireless protocols such as GPRS, Wi-Fi, Bluetooth, and 3G.